2020
DOI: 10.1186/s43058-020-00021-9
|View full text |Cite
|
Sign up to set email alerts
|

Reporting health research translation and impact in the curriculum vitae: a survey

Abstract: Background: Increasingly, health researchers must demonstrate the impact and real-life applications of their research. We investigated how health researchers with expertise in knowledge translation report research translation activities and impact on their curriculum vitae (CV). Methods: We conducted a cross-sectional survey of health researchers with expertise in knowledge translation as we anticipated best practices in CV reporting from this specialized group. Our survey asked participants about their report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…( Table 2 ). In most studies, participants in CPD activities consisted of interprofessional groups (30/52, 60%) [ 7 , 9 - 11 , 19 , 21 , 27 , 28 , 31 , 35 , 37 , 41 , 43 , 44 , 46 , 47 , 50 , 51 , 53 , 55 - 61 , 63 , 64 , 66 - 68 ]. Professions included nurses (5/52, 10%) [ 26 , 29 , 30 , 48 , 54 ], physicians (4/52, 8%) [ 38 , 39 , 49 , 52 ], social workers or other health professionals, namely occupational therapists, physiotherapists, dietitians, behavioral counselors, nutritionists, health researchers (4/52, 8%) [ 23 - 25 , 34 , 36 ], specialist physicians (3/52, 6%) [ 32 , 40 , 65 ], and pharmacists (2/52, 4%) [ 22 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example is the International School on Research Impact Assessment (ISRIA), which is intended to assist organizations in conducting effective research impact assessments for any scientific domain [ 32 ]. Structured CV templates that include research translation activities could also address existing inconsistencies in reporting impact [ 33 ].…”
Section: Discussionmentioning
confidence: 99%